An African scholar in the Netherlands East Indies al-Shaykh Ahmad Surkitti (1876–1943): his life, thoughts, and reforms - Abu Shouk, Ahmed Ibrahim (Northerwestern University Press, 2011)
Shaykh Ahmad Muhammad al- Surkitti (1876–1943) was an important figure in the Islamic reform movement in early twentieth- century Indonesia. He was born in the Sudan in 1876, studied in Mecca and Madinanfor fourteen years (1897–1911), and established his career as a schoolnteacher and a celebrated reformist leader in Indonesia (1911–1943).nThe purpose of this article is to examine the early life and career of al-Surkitti in the Sudan and Saudi Arabia, and assess critically his contributionnto the islah and tajdid movements in the Malay- Indonesian world.His intellectual and religio- political discord and confl ict with the Alawi traditionalists will be investigated in the context of Hahdarmi identitynand discourse between “orthodox Islam” propagated by Surkitti and hisnfollowers and “popular Islam” that gave the Alawi sayyids special recognitionnin their home society in Hadramaut and diaspora in Indonesia.